A Microfluidic Contact Lens to Address Contact Lens‐Induced Dry Eye. Issue 11 (23rd December 2022) - Zhu, Yangzhi; Nasiri, Rohollah; Davoodi, Elham; Zhang, Shiming; Saha, Sourav; Linn, Matthew; Jiang, Lu; Haghniaz, Reihaneh; Hartel, Martin C.; Jucaud, Vadim; Dokmeci, Mehmet R.; Herland, Anna; et al.
Abstract: The contact lens (CL) industry has made great strides in improving CL‐wearing experiences. However, a large amount of CL wearers continue to experience ocular dryness, known as contact lens‐induced dry eye (CLIDE), stemming from the reduction in tear volume, tear film instability, increased tear osmolarity followed by inflammation and resulting in ocular discomfort and visual disturbances. In this article, to address tear film thinning between the CL and the ocular surface, the concept of using a CL with microchannels to deliver the tears from the pre‐lens tear film (PrLTF) to the post‐lens ocular surface using in vitro eye‐blink motion is investigated. This study reports an eye‐blink mimicking system with microfluidic poly(2‐hydroxyethyl methacrylate) (poly(HEMA)) hydrogel with integrated microchannels to demonstrate eye‐blink assisted flow through microchannels. This in vitro experimental study provides a proof‐of‐concept result that tear transport from PrLTF to post‐lens tear film can be enhanced by an artificial eyelid motion in a pressure range of 0.1–5 kPa (similar to human eyelid pressure) through poly(HEMA) microchannels. Simulation is conducted to support the hypothesis. This work demonstrates the feasibility of developing microfluidic CLs with the potential to help prevent or minimize CLIDE and discomfort by the enhanced transport of pre‐lens tears to the post‐lens ocular surface. Abstract : The soft contact lens can cause eye dryness and discomfort. This proof‐of‐concept work reports a novel microfluidic contact lens integrated with microchannels to maintain tear flow between the CL and ocular surface. External eyelid pressure is demonstrated to enhance the tear exchange between the pre‐lens tear film and the post‐lens tear film through the microfluidic contact lens.